PROGRAM PENGEMBANGAN AGRIBISNIS KEDELAI DALAM PENINGKATAN PRODUKSI DAN K PENDAPATAN PETANI - Amar K Zakaria (Badan Penelitian dan Pengembangan Pertanian, 2010)
Soybean agribusiness development program in increasing production and farmer’s income The domestic soybean production decreased continuously in the period of 19902009 in line with the sharp decline in planted area. To fulfill the domestic soybean demand, import was conducted. From the farmers’ side, the decrease in planted area shows the low participation of farmers’ in soybean planting because soybean farming is not benefited for them. Implementation of incentive policy program is one of efforts to increase soybean production towards self-sufficiency. However, increasing soybean production is not only related with the technical aspects, but it also needs strategies to strengthen farmers’ participation in soybean farming. Government policies are needed to increase farmers’ participation in soybean farming. These include improving soybean business administration, fixing floor price, intensifying extension activities, provisioning appropriate technologies, and other stimulating incentives.Keywords: Soybean agribusiness, farmers’ participation, production, income